Analisis Pengaruh Jumlah Penduduk, Jumlah Pengangguran Dan Tingkat Pendidikan Terhadap Pertumbuhan Ekonomi Di Pulau Jawa - Nurul Izzah Purnamasari, Evita (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This research aims to analyze the influence of population, population, and education level on economic growth, especially in the Java Island region. The research method used is quantitative research using relevant sources from the Central Statistics Agency or BPS. The data source combines six provinces on the island of Java with data from 2013 to 2022. Data analysis uses panel data. The results of this study show that population, unemployment, and education levels influence economic growth on the island of Java. The population, the number of unemployed people, and the level of schooling shape the quality of the workforce on Java island.